Erosion potentials of soils under different land utilization types in Anambra State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
Soil erosion by water remains a serious ecological challenge in Anambra State that often leads to destruction of farmlands and reduction of area of land available for agricultural activities; hence, the study evaluated soil erosion potential in Awka and Ifite Ogwari areas of Anambra State. Auger and core soil samples were randomly collected from each land use practice (cassava farm, grassland, and rice farm) in three replicates at 0–30 cm depth, after which the collected samples were subjected to laboratory analysis. Significant differences were determined statistically at 5% probability level.  The results showed the soils of the studied areas to be acidic. Soils in Awka and Ifite Ogwari, respectively, belonged to sandy loam and clay textural classes. Bulk density ranged from 1.73-2.02 g/cm3. The highest moisture content (8.81%) was obtained under the rice farm in Ifite Ogwari. Ksat ranged from 0.01-0.04 cm/hr, while MWD ranged from 0.34 - 0.90 mm in both sites. OC ranged from 0.36-1.12% and was highest under the cassava farm in Ifite Ogwari. DOA was higher (29.48%) in grassland of Ifite Ogwari compared to cassava farm of Awka with a value of 24.38%. Characterised by low organic carbon content and loss of structure, the studied areas were found to be erosion-prone; therefore, replenishing the soil organic carbon upon land utilisation is key to improving soil stability.
Keywords: Agriculture; Aggregate formation; Continuous cultivation; Degradation; Soil erodibility